Antibiotic-loaded hydroxyapatite scaffolds fabricated from Nile tilapia bones for orthopaedics - Atchara Khamkongkaeo; Arreerat Jiamprasertboon; Nanthawan Jinakul; Phatraya Srabua; Saran Tantavisut; Amaraporn Wongrakpanich (Elsevier, 2023)
This work aimed to develop new antibiotic-coated/ antibiotic-loaded hydroxyapatite (HAp) scaffolds for orthopaedic trauma, specifically to treat the infection after fixation of skeletal fracture. The HAp scaffolds were fabricated from the Nile tilapia (Oreochromis niloticus) bones and fully characterized. The HAp scaffolds were coated with 12 formulations of poly (lactic-co-glycolic acid) (PLGA) or poly (lactic acid) (PLA), blended with vancomycin. The vancomycin release, surface morphology, antibacterial properties, and the cytocompatibility of the scaffolds were conducted.The HAp powder contains elements identical to those found in human bones. This HAp powder is suitable as a starting material to build scaffolds. After the scaffold fabrication, The ratio of HAp to β-TCP changed, and the phase transformation of β-TCP to α-TCP was observed. All antibiotic-coated/ antibiotic-loaded HAp scaffolds can release vancomycin into the phosphate-buffered saline (PBS) solution. PLGA-coated scaffolds obtained faster drug release profiles than PLA-coated scaffolds. The low polymer concentration in the coating solutions (20%w/v) gave a faster drug release profile than the high polymer concentration (40%w/v). All groups showed a trace of surface erosion after being submerged in PBS for 14 days. Most of the extracts can inhibit Staphylococcus aureus (S. aureus) and methicillin-resistant S. aureus (MRSA). The extracts not only caused no cytotoxicity to Saos-2 bone cells but also can increase cell growth. This study demonstrates that it is possible to use these antibiotic-coated/ antibiotic-loaded scaffolds in the clinic as an antibiotic bead replacement.